2007
DOI: 10.1093/jnci/djm127
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Mortality in the United States by Education Level and Race

Abstract: Cancer death rates vary considerably by level of education. Identifying groups at high risk of death from cancer by level of education as well as by race may be useful in targeting interventions and tracking cancer disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
298
4
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 409 publications
(332 citation statements)
references
References 39 publications
25
298
4
5
Order By: Relevance
“…Continued monitoring of cervical cancer mortality by SES levels is warranted and may utilize the databases used in the current study and other administrative health record systems. 3 The major impact of HPV vaccination will take decades to manifest as vaccination coverage increases and as girls age into periods when cervical cancer risk is highest. The disparities noted in the current study may be partly addressed by clinicians through enhanced screening and continuity of care for low-resource women to facilitate treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continued monitoring of cervical cancer mortality by SES levels is warranted and may utilize the databases used in the current study and other administrative health record systems. 3 The major impact of HPV vaccination will take decades to manifest as vaccination coverage increases and as girls age into periods when cervical cancer risk is highest. The disparities noted in the current study may be partly addressed by clinicians through enhanced screening and continuity of care for low-resource women to facilitate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, progress in reducing the cervical cancer burden has been stymied among those with low versus high socioeconomic status (SES) and among blacks versus whites. [2][3][4] SES influences cancer risk factors, such as persistent human papillomavirus (HPV) infection, 5 a necessary cause of cervical cancer, as well as access to the health care system (eg, cancer prevention, screening, and treatment). 2 In addition, advanced disease stage, insurance status, and older age at diagnosis are associated with poorer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the whole male population of Sweden aged 25-74 years, this study confirms that low SES increases the risk of prostate cancer mortality. [1][2][3][4][5][6]23 Therefore, both neighborhood-and individual-level perspectives are Neighborhood deprivation and mortality X Li et al needed when studying socioeconomic factors and their relationships with prostate cancer mortality. Various mechanisms have been proposed as possible explanations for neighborhood effects on individual health.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to age, androgen levels and family history, studies have consistently shown associations between individual-level socioeconomic status (SES) and prostate cancer risk and survival. [1][2][3][4][5][6][7][8] For example, a study from Switzerland showed that patients with low occupational status had a twofold increased risk of dying from prostate cancer because of delayed diagnosis, poor examinations and less invasive treatments. 9 During the first decade of this millennium an increasing number of studies have described the separate influences of individual-and neighborhood-level SES on health.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the current study, we observed that the effect of race on receipt of multimodality therapy was confounded by uninsured status. 31,32 To allow for future interventions, mechanisms to better understand the relation between hospital volume and insurance status with the receipt of multimodality therapy are needed.…”
Section: Discussionmentioning
confidence: 99%